Penerapan Regulasi Kesehatan Rumah dan Kendalanya pada Pembangunan Rumah Sederhana Sehat - Wijaksono, Sigit (ComTech: Computer, Mathematics and Engineering Applications, 2011)
Good housing must be free from pollution and equipped with facilities such as roads, sewer, trash, clean water sources, street lights, playground, schools, worship places, meeting halls, and health center. This study aims to determine how far the level of implementation of good housing and any obstacles that arise in its application in small healthy houses, especially in Jabodetabek. The method uses a survey by taking samples from 30 healthy houses in Bojong Indah Residence, Cengkareng, West Jakarta. Data collecting uses questionnaires and interviews associated with those as required and the results obtained are general descriptions of the actual conditions about how government regulations regarding to eligibility for health residences are applied, and the factors that influence the level of its application in development.The results of this research is expected to give inputs for national and local governments in making policies related to housing.